The Impact Of Ceo Attributes On Real Earnings Management In Saudi Arabia - Boudiab, Mourad; Belhimer ,Messaoud (جامعة الوادي University of Eloued, 2025)
This research aims to investigate and determine the relationship between CEO characteristics and REM of Saudi financial firms from 2012 to 2023. Four attributes of a chief executive officer have been examined in this study: tenure, duality, ownership, and financial expertise. 504 observations throughout twelve years, from 2012 to 2023, make up the sample. CEO ownership, duality, and financial expertise have a significant negative association with real earnings management out of the four characteristics. However, the last feature of this study is CEO tenure, which the current research demonstrated to have a positive and significant relationship with real earnings management.
Keywords: CEO; real earnings management; Saudi Arabia; Financial firm